2022
DOI: 10.1101/2022.10.23.513274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adult lifespan trajectories of neuromagnetic signals and interrelations with cortical thickness

Abstract: Oscillatory power and phase synchronization map neuronal dynamics and are commonly studied to describe the healthy or diseased brain. Yet, little is known about the course of these features from early adulthood into old age. Leveraging magnetoencephalography (MEG) resting-state data in a cross-sectional adult sample (n = 350), we probed lifespan differences (18-88 years) in connectivity and power and interaction effects with sex. Building upon recent attempts to link structure and function in the brain, we tes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 122 publications
0
11
1
Order By: Relevance
“…Consistently, brain state dynamics differed between visual areas and higher-order networks 58 across the adult lifespan and were linked to cognitive performance, with a reduction in older people being more strongly associated with shifts between these states than in young people. As previously mentioned, age-related changes in the visual cortex have also been reflected in phase-based connectivity across different frequency bands 4 , but the predictive power of phase-related measures was rather poor in our study and others 26 . This may be because estimations of the phase of M/EEG signals are generally susceptible to noise, making it a less robust metric than autocorrelation, which is well-normalized between -1 and 1.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…Consistently, brain state dynamics differed between visual areas and higher-order networks 58 across the adult lifespan and were linked to cognitive performance, with a reduction in older people being more strongly associated with shifts between these states than in young people. As previously mentioned, age-related changes in the visual cortex have also been reflected in phase-based connectivity across different frequency bands 4 , but the predictive power of phase-related measures was rather poor in our study and others 26 . This may be because estimations of the phase of M/EEG signals are generally susceptible to noise, making it a less robust metric than autocorrelation, which is well-normalized between -1 and 1.…”
Section: Discussioncontrasting
confidence: 53%
“…Furthermore, we observed a decrease in autocorrelation in the temporal cortex, particularly in the age groups after 40 years of age. Again, previous studies have identified the temporal cortex as an area associated with strong M/EEG power increases across the adult lifespan 3,4 , with an increase over the adult lifespan.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations